Cell Polarity 1 Biological Role and Basic Mechanisms - Ebnet, Klaus; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This work provides a state-of-the art overview on the most relevant aspects of cell polarity. Volume 1 addresses cell polarity and cell migration (front-rear polarity), cell polarity and barrier formation (apico-basal polarity) and neuronal polarity. It particularly focuses on cell polarity at the molecular level and the underlying molecular mechanisms. It also elaborates the common principles and mechanisms that regulate cellular polarization in different cell types and contexts. Both volumes are intended for professors, group leaders and researchers in cell biology as well as medical professionals in the fields of anatomy, cell biology, physiology, pathology and tumor biology.
The PAR3-aPKC-PAR6 Complex -- PAR-1 Kinase and Cell Polarity -- The Crumbs3 Complex -- The Scribble–Dlg–Lgl Module in Cell Polarity Regulation -- Front-to-Rear Polarity in Migrating Cells -- Neuronal Polarity -- Epithelial Apicobasal Polarity in the Drosophila Embryo -- The Polarized Distribution of the Na+,K+-ATPase -- Endothelial Cell Polarization During Lumen Formation, Tubulogenesis and Vessel Maturation in 3D Extracellular Matrices -- Phosphoinositides as Determinants of Membrane Identity, Apicobasal Polarity and Lumen Formation -- Immunological Synapse Formation: Cell Polarity During T Cell–APC Interaction -- Homotypic Cell–Cell Interactions and Apicobasal Polarity in Epithelial Cells and Endothelial Cells -- Cell–Cell Interactions, Cell Polarity and the Blood–Testis Barrier -- Membrane Traffic and Apicobasal Polarity in Drosophila Epithelial Cells -- Roles of Rab Family Small G Proteins in Formation of the Apical Junctional Complex in Epithelial Cells -- Protein Trafficking in Polarized Epithelial Cells.
Keywords: Cell physiology; Cancer research; Human physiology; Cell Physiology; Cancer Research; Human Physiology